A Retrospective of Global Navigation Satellite System Ionospheric Irregularities Monitoring Networks in Brazil - de Paula, Eurico Rodrigues; Monico, João Francisco Galera [UNESP]; Tsuchiya, Ítalo Hirokazu [UNESP]; Valladares, Cesar Enrique; Costa, Sônia Maria Alves; Marini-Pereira, Leonardo; Vani, Bruno César; Moraes, Alison de Oliveira (FapUNIFESP (SciELO), 2023)
The use of Global Navigation Satellite System (GNSS) for air and terrestrial navigation and for many applications is increasing in the last decades. However, the Earth’s ionosphere causes GNSS signal delay due to the total electron content (TEC) and scintillation in the signal phase and amplitude. This scintillation can give rise to deleterious effects in the GNSS positioning. So, it is important to assess the effects of the ionosphere over the GNSS signal. To achieve this goal, it is necessary to have a large spatial and temporal coverage of data from many different sounders, being the GNSS receivers of great importance due to their global coverage and availability. In this work, we present a retrospective of the scintillation monitoring networks in Brazil and their characteristics. As the RBMC network managed by the IBGE provides TEC and as rate of TEC index (ROTI) is well correlated with ionospheric irregularities, we present also the RBMC network description. These RBMC GNSS receivers provide data in regions with scarcity of scintillation monitors. The description of the Ionospheric Scintillation Monitoring Receivers (ISMR) Query Tool, that is a web software that has been supporting research on the ISMR data, is also presented.
Keywords: Equatorial plasma bubbles; Geophysical instrumentation; Ionospheric scintillation; Satellite navigation; Space weather monitoring